Inventory insects of sorghum plantation in Northern Sumatera, Indonesia. Issue 1 (1st June 2022) - Siregar, A Z; Tulus,; Yunilas,; Nisa, S C A
Abstract: The purpose of this research was to invent types and abundance insects in sorghum plantation in Lalang Village, Rambutan District, Tebing Tinggi from July to August 2021, with an area of 12 m × 12 m. Insects were collected using sweep traps, pit fall traps, light traps and yellow sticky traps. The collected insects were collected and then were identified. Data analysis was carried out by descriptive quantitative with Purposive Random Sampling (PRS), which identified in the Pest labouratory-USU. The results research identified was four insects Orders (Coleoptera, Diptera, Hemiptera and Lepidoptera) with 9 families (Chrysomelidae, Scarabaeidae, Cecidomyiidae, Muscidae, Aphidae, Dephiciodae, Pentatomidae, Noctuidae, Pyraliidae) and 16 species. The highest insect pest population was at the time of the sixth sampling as many as 634 individuals/plot, the predator population was 248 individuals/plot, and the parasitoid population was 118 individuals. Calculation of richness index R1yst=8.49: R1sn=7.65, eveness index (Eyst=0.59; Esn=0.48) and insects diversity Shannon-Wiener index (H'yst=2.56; H'n=2.13). Then the parameter environmental measure of temperature (30.3-36.2°C), humidity (82-90%) were carried out during the sorghum plantation period.